2004
DOI: 10.1074/jbc.m403133200
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Determinants of Target Gene Specificity in Myb Transcription Factors

Abstract: The A-Myb and c-Myb transcription factors share a highly conserved DNA-binding domain and activate the same promoters in reporter gene assays. However, the two proteins have distinct biological activities, and expressing them individually in human cells leads to the activation of distinct sets of endogenous genes, suggesting that each protein has a unique transcriptional specificity. Here, the structural and functional features of the Myb proteins were compared, using assays of endogenous gene expression to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 39 publications
5
82
0
Order By: Relevance
“…19 GSEA revealed a significant overlap between the Fra-1-derived gene sets and the genes upregulated in EpRas cells upon TGF-β-induced EMT 21 (Table 1a). Genes associated with c-Myb 29 or with promoters occupied by Smad2/3, 30 two TFs connected to TGF-β and EMT, 31,32 were also enriched (Table 1b) Figure S6a, Figures 5a and b). Slug, encoded by snai2, was also increased (Figures 5a and b), whereas mRNA of snai1/Snail was moderately elevated and the protein undetectable (Figure 5a and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…19 GSEA revealed a significant overlap between the Fra-1-derived gene sets and the genes upregulated in EpRas cells upon TGF-β-induced EMT 21 (Table 1a). Genes associated with c-Myb 29 or with promoters occupied by Smad2/3, 30 two TFs connected to TGF-β and EMT, 31,32 were also enriched (Table 1b) Figure S6a, Figures 5a and b). Slug, encoded by snai2, was also increased (Figures 5a and b), whereas mRNA of snai1/Snail was moderately elevated and the protein undetectable (Figure 5a and data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Use of different assay systems may also be expected to yield different results since complex chromatin structure is largely maintained in ChIP assays whereas a relatively small probe devoid of histones was used for gel shift assays assessing the CD13 promoter. This may be particularly relevant in the case of c-Myb where complex structural elements appear to influence its activity [60].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the requirements of this domain but point mutations suggest that acidity of the residues is not essential and conformation is of critical importance [135]. In addition, recent studies demonstrated that undefined regulatory elements within the transactivation domain control promoter specific target gene expression [154].…”
Section: C-mybmentioning
confidence: 99%
“…Upon examination of the lists of genes that were up or down regulated in c-Myb deficient and sufficient thymocytes, we identified a number of genes previously reported as c-Myb transcriptional targets in other cell types and model systems including Nras [326], Vcl [154], CD53 [256], Cdkn1a [154], Cbx4 [256], Ets2 [327], Bcl2 [232,233,256,328], and Itga4 [304]. However, only Cbx4 and Bcl2 were reported to be direct c-Myb targets as demonstrated by a ChIP of endogenous c-Myb from promoters in a multipotent hematopoietic cell line FDCP-mix [256].…”
Section: Btg1mentioning
confidence: 99%
See 1 more Smart Citation